The Impact of Previous Knowledge and Art Exposure on Self-Efficacy in Art Education: A Study of Pre-Service Teacher Trainees - Duarah, Devajani; Choudhury, Smritishikha; Deka, Dipanwita (Voices of Teachers and Teacher Educators, 2024)
This research investigated the effect of art knowledge and art exposure of pre-service teacher trainees on their self-efficacy in teaching and integrating art education in Assam, India, with 250 participants at District Institutes of Elementary Teachers’ Training (DIETs). Arts knowledge correlates positively with increased self-efficacy, with art exposure also positively influencing self-efficacy. Significantly, art knowledge emerges as the more accurate predictor of self-efficacy. Implications for teacher education include prioritizing comprehensive art education with hands-on experiences and interdisciplinary strategies, in light of India’s National Education Policy (NEP) 2020 and the National Curriculum Framework for School Education (NCFSE) 2023, thereby advancing art education for educators and students.